(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Teacher is the pivot of civilization` as said by Dr. S. Radha Krishnan, every teacher has the primary goal to shape the future of his/her learners. His/her role begins with the student in particular and culminates in society in general. In order to attain perfection in any given field one need a guide, teacher or a coach to mentor in the stages of learning. More specifically the teacher of English has more responsibilities on his/her part to teach the content in respect of grammar and pronunciation for accuracy and fluency body language in respect of decency and to train the students in a committed and devoted manner and transform into competent students to face challenges in career capture and life settlement. The present paper discusses the different approaches in language teaching and defines different learning strategies and emphasizes the importance of learning strategies. This paper concludes with the best learning strategies adopted by the good learners in learning English as a foreign or second language.No one can dispute the assertive position of English as a communicative language. It is enjoying status of medium of instruction as well as compulsory subject in Pakistan. But it is facing numerous problems in learning. The failure rate of the students is increasing which is deplorable. The failure in this subject means the failure in the public examinations. The concerns about the situation can be observed by all the stakeholders. Many factors have been indicated that are responsible for creating obstacles in learning English. Results point out that students of the context desire to learn English but numerous factors stand on their way of progress that need to be eradicated for the better future of this language.